What are the ethical issues in relation to the role of the family in intensive care? - Quenot, Jean-Pierre; Ecarnot, Fiona; Meunier-Beillard, Nicolas; Dargent, Auguste; Large, Audrey; Andreu, Pascal; Rigaud, Jean-Philippe (Annals of Translational Medicine; Vol 5, Supplement 4 (December 22, 2017): Annals of Translational Medicine (Focus on “Ethical Issues in Intensive Care”), 2017)
A large proportion of patients admitted to the intensive care unit (ICU) are unable to express themselves, often due to acute illness, shock or trauma, and this precludes any communication and/or consent for care that might reflect their wishes and opinions. In such cases, the only solution for the ICU physician is to include the patient’s family in the healthcare decisions. This can represent a significant burden on the family, on top of the psychological distress of the ICU environment and hospitalisation of their relatives, and many family members may suffer from anxiety, depression or symptoms of post-traumatic stress disorder (PTSD) during or after the hospitalisation and/or death of a loved one in the ICU. Good communication remains the cornerstone of family satisfaction in the ICU. Information imparted to the patient and/or family should cover diagnosis, prognosis and treatment. Information should be given orally, in person, using accessible language. Several other measures that can lessen the burden on the families of patients in the ICU and help to reduce anxiety and stress are also detailed in this review. Overall, family-centred care in the ICU requires a systematic communication strategy within the healthcare team, combined with an environment that is as amenable as possible to the family’s presence and involvement, in order to maximize family satisfaction with ICU care, and ensure that the patient’s values and preferences are respected.